PENGGUNAAN MEDIA PEMBELAJARAN ( PAPAN MUSI ) PADA MATERI PERKALIAN DALAM MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA PELAJARAN MATEMATIKA - Desty Shintia Agustina (Al-Aulad: Journal of Islamic Primary Education, 2025)
This study addresses the challenge of low mathematics learning outcomes and limited student interest in multiplication among second-grade students at MI Al-Amin. A qualitative descriptive approach was adopted, involving 20 students selected through purposive sampling. Data collection methods included observation, interviews, and documentation to evaluate the impact of using the Papan Musi instructional media. The findings indicated that the use of Papan Musi demonstrated potential effectiveness in enhancing students’ understanding of multiplication. Visual and hands-on learning approaches appeared to increase student engagement, enthusiasm, and comprehension. This was evidenced by improvements in daily test scores and supported by positiv feedback from students, who reported greater enjoyment and clarity in learning. Although not without limitations, such as visibility issues and classroom noise, the overall response suggested that Papan Musi may serve as a useful tool to support concept acquisition in early mathematics education.